Adoption of Cyber Extension by Agricultural Extension Workers (PPL) and Factors Affecting - Budi Cahyono; Retno Setyowati; Hanifah Ihsaniyati (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2020)
Cyber Extension has an important role to play in helping agricultural counsellors carry out their duties in this digital age. Initial surveys at the research site showed only 15% of Agricultural Extension Centers (BPP) adopted Cyber Extension. Information regarding the overall adoption of PPL is not yet clearly known. The study of adoption and the factors that influence the adoption of PPL is very important known. Therefore, the purpose of this study is to analyze the influence among cyber extension adoption variables within the framework of the Technology Acceptance Model (TAM) model. This research is classified as explanatory research with quantitative approach. Sampling technique using simple random sampling that was number of 140 people PPL Civil Servants and THL. The influence test between variables (hypothetical test) is conducted with t-test with a confidence level of 95% (α = 0.05). The results showed there were 8 accepted hypotheses (significant effect) and 2 rejected hypotheses (insignificant effect).